2012
DOI: 10.1093/carcin/bgs110
|View full text |Cite
|
Sign up to set email alerts
|

A novel prenylflavone restricts breast cancer cell growth through AhR-mediated destabilization of ERα protein

Abstract: There is concern that ingestion of dietary phytoestrogens may increase risk of estrogen receptor alpha (ERα)-positive breast cancer. The prenylflavone icaritin, a phytoestrogen consumed in East Asian societies for its perceived beneficial effects on bone health, stimulated the growth of breast cancer (MCF-7) cells at low concentrations. Although acting like an estrogenic ligand, icaritin exerted an unexpected suppressive effect on estrogen-stimulated breast cancer cell proliferation and gene expression at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…We and others have reported extensive interrelationships between ERα and AhR complexes in regulation of target genes and cell proliferation of breast cancer cells (Liu et al, 2006; Madak-Erdogan and Katzenellenbogen, 2012; Tiong et al, 2012). In addition, we found that in breast cancer cells, the expression of AhR target genes was decreased by E2 whereas here we found that soy BEs and liquiritigenin stimulated AhR target gene expression, as did the potent AhR agonist TCDD/dioxin.…”
Section: Discussionmentioning
confidence: 95%
“…We and others have reported extensive interrelationships between ERα and AhR complexes in regulation of target genes and cell proliferation of breast cancer cells (Liu et al, 2006; Madak-Erdogan and Katzenellenbogen, 2012; Tiong et al, 2012). In addition, we found that in breast cancer cells, the expression of AhR target genes was decreased by E2 whereas here we found that soy BEs and liquiritigenin stimulated AhR target gene expression, as did the potent AhR agonist TCDD/dioxin.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies demonstrated that icaritin exhibits multiple kinds of pharmacological and biological activities, including neuronal protection against myloid-induced neurotoxicity (Wang et al 2007), induction of embryonic stem cells differentiation into cardiomyocytes (Zhu and Lou 2005), suppression of steroid-associated osteonecrosis and osteoclastic differentiation (Huang et al 2007;Chen et al 2018), self-renewal of mouse embryonic stem cells (Tsang et al 2017), and improvement of hematopoietic function . Recently, icaritin has been shown an antitumor effect of icaritin in various solid tumors, such as lung cancer (Zheng et al 2014), hepatocellular carcinoma (Sun et al 2015;Hu et al 2016;Lu et al 2017), breast cancer (Guo et al 2011;Tiong et al 2012), esophageal cancer , and glioblastoma Liu et al 2018). Except for the studies of icaritin on the solid tumors, icaritin has also been demonstrated a significant inhibitory effect on multiple hematological cancer cells, including leukemia, lymphoma and multiple myeloma (Zhu et al 2011;Li et al 2013;Yang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Icaritin is a prenylflavonoid derivative from a traditional Chinese herb, Epimedium Genus. Recently, accumulating studies have demonstrated an anti-tumor effect of icaritin in various cancers, including solid tumors and hematological cancers, such as lung cancer (Zheng et al 2014), hepatocel-lular carcinoma (Sun et al 2015;Hu et al 2016;Lu et al 2017), breast cancer (Guo et al 2011;Tiong et al 2012), esophageal cancer (Han et al 2018), glioblastoma Liu et al 2018), leukemia and lymphoma (Zhu et al 2011;Li et al 2013;Li et al 2014;Wu et al 2015;Zhu et al 2015;Yang et al 2019). Icaritin exerts its anti-tumor effects in various cancers mainly by inhibiting cell proliferation, inducing cell differentiation and apoptosis, suppressing cell migration and invasion (Zheng et al 2014;Xu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe any significant change in CYP1B1 expression in the ovary or liver but CYP1A1 (undetectable in chicken ovary) expression was upregulated in the liver of whole flaxseed-fed birds (Figure 4B). In addition, it has been very well established that AHR can promote ER α destabilization by targeting it for proteasomal degradation by ubiquitin ligase [46]. …”
Section: Discussionmentioning
confidence: 99%